Pelaksanaan Standar Kompetensi Lulusan di UPT SPF-SD Inpres Mangga Tiga Makassar - Nur Sakina Mawadda; Wahira Wahira; Syamsurijal Basri (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study examines the Implementation of Graduate Competency Standards at the UPT-SPF SD Inpres Mangga Tiga Makassar. This study aims to determine the Implementation of Graduate Competencies at the UPT SPF SD Inpres Mangga Tiga Makassar. The approach in this study uses a qualitative approach with a descriptive research type. The data sources in this study are the Principal and Teachers. Data collection techniques include interviews, observations, and documentation. The results of the study show that: 1). Students demonstrate positive attitudes, discipline, responsibility, and respect for moral values through compliance with regulations, group work, and participation in social and religious activities. 2). Students gain knowledge through the use of technology, developing creativity through art, and introducing local culture that supports dynamic learning, social skills, and cultural awareness. 3). Students develop creativity, analytical skills, and social skills developed through art, technology, problem-based learning, and structured group work with teacher evaluation. 4). The improvement of graduate competency standards is supported by adequate infrastructure, parental support, relevant curriculum, improving teacher quality, and the active role of the management team through educational quality assurance and collaboration with related parties. 5). Barriers to improving graduate competency standards include limited teacher competency, student motivation, and financial challenges. The management team addresses these challenges through teacher training, discussions, extracurricular activities, and increased communication with parents and student support.   Abstrak Penelitian ini mengkaji tentang Pelaksanaan Standar Kompetensi Lulusan di UPT-SPF SD Inpres Mangga Tiga Makassar. Penelitian ini bertujuan untuk mengetahui Pelaksanaan Kompetensi Lulusan di UPT SPF SD Inpres Mangga Tiga Makassar. Pendekatan dalam penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Sumber data pada penelitian ini Kepala Sekolah dan Guru. Teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa : 1). Peserta didik menunjukkan sikap positif, disiplin, tanggung jawab, dan menghargai nilai moral melalui kepatuhan tata tertib, kerja kelompok, serta partisipasi dalam kegiatan sosial dan keagamaan. 2). Peserta didik memperoleh pengetahuan melalui pemanfaatan teknologi, pengembangan kreativitas melalui seni, serta pengenalan budaya lokal yang mendukung pembelajaran dinamis, keterampilan sosial, dan kesadaran budaya. 3). Peserta didik mengembangkan kreativitas, keterampilan analitis, dan sosial yang dikembangkan melalui seni, teknologi, pembelajaran berbasis masalah, serta kerja kelompok terstruktur dengan evaluasi guru. 4). Peningkatan standar kompetensi lulusan didukung oleh sarana prasarana memadai, dukungan orang tua, kurikulum relevan, peningkatan kualitas guru, serta peran aktif tim pengelola melalui penjaminan mutu pendidikan dan kolaborasi dengan pihak terkait. 5). Hambatan peningkatan standar kompetensi lulusan meliputi keterbatasan kompetensi guru, motivasi siswa, dan tantangan biaya. Tim pengelola mengatasinya melalui pelatihan guru, diskusi, ekstrakurikuler, serta peningkatan komunikasi dengan orang tua dan dukungan bagi siswa.